Diversity And Molecular Characterization Of Termite Gut Symbionts In Globitermes Sulphureus Haviland (Blattodea: Termitidae) - Hussin, Nurul Akmar (2020)
Globitermes sulphureus (Haviland) is a higher group termite and is known as a major pest in agricultural areas especially in coconut and palm oil plantations. Globitermes sulphureus was also found in infesting the wood building structure in rural and urban areas. Despite its pest status, the information about this cryptic insect in term of genetic and gut symbionts are still limited. In this study, the COII sequences of G. sulphureus was amplified to study the phylogenetic relationship between five termite colonies in the USM Penang campus